Caution: Baby on Board. Issue 5 (1st December 2014) - Redelmeier, Donald; May, Sharon
Abstract: Statistical analysis suggests that pregnant women are at greater risk of traffic incidents. Is "baby brain" to blame – or is this an outrageous insult? Donald Redelmeier and Sharon May investigate